Trastuzumab deruxtecan in patients with active brain metastases from HER2-positive/low metastatic breast cancer: a retrospective multicenter real-world study - Fangfang Duan; Xin Hua; Wei Lu; Xingxing Gui; Jingdun Xie; Xudong Wang; Yuyu Ma; Wenyu Zhai; Wen Xia (Breast Cancer Research)
Abstract Background Brain metastases (BMs) are almost a norm and devastating complication of metastatic breast cancer (MBC), but patients with active BMs (untreated or progressing to prior local therapy) are usually excluded from participating in clinical trials. Trastuzumab deruxtecan (T-DXd) has shown remarkable intracranial activity in pretreated human epidermal growth factor receptor 2 (HER2)-positive MBC with active BMs in latest prospective trials, but real-world evidence about its efficacy and safety remains limited. Methods This real-world study enrolled patients with active BMs from HER2-positive/low MBC receiving at least one cycle T-DXd (5.4 mg/kg, Q3W) in three hospitals in China between June 2022 to May 2024. The primary endpoint was the best intracranial overall response rate (iORR) following the response assessment in neuro-oncology brain metastases criteria. Secondary endpoints included the intracranial and overall progression-free survival (iPFS-PFS), overall survival (OS), and safety. Results In total, 38 patients were enrolled, including 29 HER2-positive and 9 HER2-low MBC. Except for endocrine therapy, the median number of prior therapy lines was 2 (range 0–10). Among HER2-positive patients, one patient (11.1%) had a complete intracranial response and eighteen (62.1%) had a partial intracranial response as the best intracranial response, with an iORR of 65.5%. As for HER2-low patients, the iORR was 66.7%. During a median follow-up of 10.3 (range 1.53–24.4) months, the median iPFS and OS were not reached for both HER2-positive and HER2-low MBC, their 12-month iPFS rate stood at 79.8% (95% confidence interval (CI): 65.2–97.7%) and 51.9% (95% CI: 26.7–100.0%), respectively. In the HER2-positive cohort, the median PFS was 12.8 months (95% CI: 10.2-not reached) and the 12-month OS rate was 86.5% (95% CI: 69.4–100.0%). For HER2-low cohort, the median PFS and 12-month OS rate were 6.33 months (95% CI: 3.93-not reached) and 85.7% (95% CI: 63.3–100.0%), respectively. Most common adverse events were moderate and no new safety signals were observed. Conclusions In this real-world population, T-DXd yielded encouraging intracranial activity in HER2-positive/low MBC patients with active BMs with acceptable tolerance, which was aligned with previous clinical trials data. These results support the concept of T-DXd as systemic therapy for MBC patients with active BMs irrespective of HER2-positive/low.